Kognitive Aspekte des Übersetzungsprozesses: Eye-Tracking im interkulturellen Vergleich - Lee, KyeongHwa (Frank & Timme eBooks, 2022)
What happens in the mind when we translate? And how does our mother tongue influence our speaking, writing, thinking and translating? In the answer to one question lies the resolution of the other. KyeongHwa Lee has explored both questions using eye tracking, writing process analysis, and a survey of study participants. She can prove that people of different native languages store and process the information of a sentence in different ways. The syntactic structure and the information structure of their respective native language obviously play a decisive role. They influence how we understand texts, how we speak and write, and how we translate from one language to another. Similar sentence structure of working languages apparently facilitates the language transfer process. But the influence of the mother tongue goes far beyond that: it also shapes our thinking.